Financial Analysts' Forecast Accuracy : Before and After the Introduction of AIFRS - Chee Seng Cheong; Mahmud Al Masum (Australasian Accounting, Business and Finance Journal, 2010)
We examine whether financial analysts’ forecast accuracy differs between the pre- and post- adoption of Australian Equivalents to the International Financial Reporting Standards (AIFRS). We find that forecast accuracy has improved after Australia adopted AIFRS. As a secondary objective, this paper also investigates the role of financial analysts in reducing information asymmetry in today’s Australian capital market. We find weak evidence that more analysts following a stock do not help to improve forecast accuracy by bringing more firm-specific information to the market.
Keywords: Analysts’ forecasts; AIFRS; Forecast errors; Intangible assets